Tác động của phát trực tiếp trên TikTok đến mua sắm ngẫu hứng thông qua sự hứng khởi - Kiều Anh, Tài; Lý Phước, Sang (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
This study simultaneously investigates important stimuli aspects such as livestreamer, livestream environment, and livestream content factors that drive arousal and impulsive purchase. The study also examines the moderating role of fear of missing out on the relationship between arousal and impulsive purchase. The study conducted a survey of TikTok users in Vietnam having made impulsive purchases in livestream sessions, yielding 338 valid responses used to test the research model using partial least squares structural equation modeling. Findings show that livestream environment and content factors significantly enhance viewers’ arousal, which in turn stimulates impulsive purchase. However, streamer attractiveness and credibility do not have a significant effect on viewers’ arousal; nor does the moderating impact of fear of missing out on the relationship between arousal and impulsive purchase. This study not only enriches consumer behavior literature in the livestream commerce context but also provides practical implications for digital marketers, livestream sellers, and platform administrators.